Potential autofertility in true hermaphrodites - Bayraktar, Zeki (Taylor and Francis Ltd., 2018)
This article examines the studies on the pregnancies of true hermaphrodites and self-fertilization in hermaphrodite mammals that have been published in the last 40years. The number of hermaphrodite pregnants reported in the literature since 1975 was 14, the number of pregnancies was 26 and the number of healthy born babies was 20. All of the babies that were born were male. The pregnancy developed following gonadectomy in seven cases (nine pregnancies). In some cases, either gonadectomy was not performed at all or it was performed after pregnancy (eight cases, 17 pregnancies). The karyotype was 46,XX in four of these eight cases that became pregnant despite in situ ovotestis while it was 46,XX/46,XY in the other four cases (chimera). In the literature, pregnancy cases that developed through self-fertilization were not reported in humans. However, autofertilization was detected in mammalian hermaphrodites such as domestic rabbit. Furthermore, the ovarian tissues of true hermaphrodites were mainly functional and ovulatory. The testicular tissues were mainly immature. However, spermatogenesis was determined in some cases. In fact, both ovulation and spermatogenesis were detected in some cases. All of these findings show that true hermaphrodites with ovarian and testicular tissues are potentially autofertile.
Keywords: Hermaphroditism; Self-Fertilization; Autofertilization; Chimera